Analisis Break Even Point sebagai Alat Perencanaan Laba pada Usaha “Hawa Butik Makassar” - Iqranul Citrana; Nuraisyiah; Masdar Ryketeng (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2026)
This study aims to analyze the Break-Even Point (BEP) as a profit planning tool at Hawa Butik Makassar. This study employs a qualitative approach, focusing on data related to Break-Even Point analysis, including costs, sales, and net profit. Data collection techniques were conducted through interviews, documentation, and direct observation at Hawa Butik Makassar. Data analysis was performed by calculating the Break-Even Point, contribution margin, and margin of safety to determine the business’s ability to achieve profit targets. The results indicate that Break-Even Point analysis can serve as an effective profit planning tool for Hawa Butik Makassar. Through Break-Even Point calculations, management can determine the minimum sales level required to avoid losses and set sales targets to achieve desired profits. Additionally, the analysis of contribution margin and margin of safety provides useful information for evaluating the level of sales security and supports decision-making regarding cost control and future sales planning. Thus, the application of Break-Even Point analysis can help improve the effectiveness of profit planning and the sustainability of Hawa Butik Makassar.